Strategi Penyelenggaraan Perpustakaan Keliling dalam Meningkatkan Minat Baca Masyarakat (Studi Kasus di Pustaka Gua Hira Nagari Kepala Hilalang Kecamatan 2x11 Kayutanam Kabupaten Padang Pariaman) - Nur Anisa (Jurnal Pustaka Ilmiah, 2021)
This study aims to describe the implementation of the Pustaka Gua Hira mobile library to increase people's interest in reading. As well as to find out the obstacles and efforts in increasing people's interest in reading. This research uses descriptive method with qualitative research. Data collection techniques used are in the form of observation data, interviews, and documentation. Meanwhile, the data validation technique used is triangulation. The data analysis technique used in this study was data reduction, data presentation, and conclusion drawing. The results of this study are the lack of collection of library materials in the Hira Cave Library, the implementation of the mobile library of Hira Cave Library is not carried out evenly due to the lack of collections so that there is a lack of reading interest in the community in Nagari Kepala Hilalang.